2016
DOI: 10.1001/jamapsychiatry.2016.0178
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-Related Disruption of Functional Topography of Striatal Connections in Unmedicated Patients With Schizophrenia

Abstract: Importance Despite the well-established role of striatal dopamine in psychosis, current views generally agree that cortical dysfunction is likely necessary for the emergence of psychotic symptoms. The topographical organization of striatal-cortical connections is central to gating and integration of higher-order information, so a disruption of such topography via dysregulated dopamine could lead to cortical dysfunction in schizophrenia. However, this hypothesis remains to be tested using multivariate methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 46 publications
(53 reference statements)
5
44
0
Order By: Relevance
“…Overall, in the present study we found novel evidence of decreased resting-state functional connectivity between the striatum and the cortical default mode network in psychosis risk. This adds to other research implicating the dorsal caudate as a region where decreased connectivity to cortical regions is associated with psychosis (e.g., Horga et al, 2016). The present findings also appear to be generally consistent with the aberrant-salience view of psychosis (Kapur, 2003), and with evidence of self-relevance processing disturbances in psychosis risk and psychotic disorders (Nelson et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…Overall, in the present study we found novel evidence of decreased resting-state functional connectivity between the striatum and the cortical default mode network in psychosis risk. This adds to other research implicating the dorsal caudate as a region where decreased connectivity to cortical regions is associated with psychosis (e.g., Horga et al, 2016). The present findings also appear to be generally consistent with the aberrant-salience view of psychosis (Kapur, 2003), and with evidence of self-relevance processing disturbances in psychosis risk and psychotic disorders (Nelson et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…In this perspective, early-onset alterations of experience-dependent plasticity would interfere with structural and functional connectivity subserving the acquisition of basic neurological and socio-cognitive skills in DS Galderisi et al, 2008;Peralta et al, 2014;Wheeler et al, 2015). The onset of psychosis might add to this altered connectivity producing a further impairment in brain plasticity related to abnormal salience attribution to stimuli and events with no intrinsic reward value (Horga et al, 2016;Howes and Kapur, 2009). If PNS and DS are the results of pervasive neurodevelopmental disorders, the implication for treatment are complex: a combination of psychosocial rehabilitation programs and techniques to improve brain plasticity should be implemented to favor the development of never-acquired functions and facilitate experience-dependent plastic changes to re-shape functional and structural connectivity within relevant networks.…”
Section: Discussionmentioning
confidence: 99%
“…ume, reduced fractional anisotropy(Levitt et al, 2017;Quide, Morris, Shepherd, Rowland, & Green, 2013), increased synaptic dopamine function(Horga et al, 2016;Meyer-Lindenberg et al, 2002), increased glutamate levels (de la Fuente-Sandoval et al, 2013), and lower activations or connectivity(Mucci et al, 2015;Peters et al, 2017;Zhou et al, 2007), most of those previous studies recruited chronic patients, or the early-stage SZ patients who had already received the antipsychotic medications. Therefore, the current finding of lacking the associative loop impairment in medication-naïve FESZ suggested that associative loop and their related cognitive function may be progressively present with the development of disease and mainly in the field of active consciousness.…”
mentioning
confidence: 99%